2020
DOI: 10.1080/1331677x.2020.1746190
|View full text |Cite
|
Sign up to set email alerts
|

Do house prices squeeze marriages in China?

Abstract: This study reviews the threshold effect of house prices (HPs) on marriage (MR) in China by utilizing a panel threshold regression. The findings indicate that HPs have a positive impact on MR when the price is below the threshold value. Homeownership is an extremely important factor in MR in China, and MR without housing is considered incomplete. However, HPs have a negative effect on MR when the price is higher than the threshold value. Unemployment and female education have a negative effect on MR, while GDP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…There are several theoretical models explaining the potential relationship between house prices and marriage. Here, we follow the duration model [29,[31][32][33]. Rising house prices can have a negative effect on marriage, which is in line with the budget constraint on household consumption.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several theoretical models explaining the potential relationship between house prices and marriage. Here, we follow the duration model [29,[31][32][33]. Rising house prices can have a negative effect on marriage, which is in line with the budget constraint on household consumption.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…However, all of these studies consider microdata, and, to the best of our knowledge, only two have examined the link between house prices and marriage using panel data from a sample of a country's provinces [1,29]. This aggregate perspective seems vital, because, in many countries, housing markets and policies have strong regional features.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the unidentifiable test, the estimated coefficients all passed the significance test. At the same time, according to the method [40], this paper also uses the lagging period of the industrial integration variable as an instrumental variable to carry out the two stage least square method test. The regression results in Column 2 of Table 4 can still reach the same conclusion.…”
Section: Endogenous Testmentioning
confidence: 99%
“…Clark, Yi and Zhang (2020) analyzed a panel data of 35 large cities from 2013 to 2017 in China and found that there was an approximately 0.94-percentage-point decrease in the probability of having a child under two with a 1 percent increase in housing prices. By conducting a panel threshold model, Su et al (2020) found that housing prices had a negative impact on marriage when the price was above the threshold value.…”
Section: Literature Reviewmentioning
confidence: 99%